REVITALISASI PERMAINAN TRADISIONAL BALI SEBAGAI BAGIAN DARI ATRAKSI WISATA BUDAYA DI KOTA DENPASAR - Primayoga Arya, Putu Aditya (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 02, Januari 2015, 2015)
Recently, several traditional games suffer a setback as an impact of vast growing of modern, digital, and online games. This phenomenon raises a call to revitalise traditional games not only in order to strengthenen of folk cultures but also to promote them as tourist attractions. This article analyses attempts to revialise traditional games in the urban Denpasar, the capital city of Bali. The design of this study was descriptive qualitative by doing an observation, conducting a survey through spreading some questionnaires, depth interview and library research. The primary data sources were tradional games practioners, community leaders who have experiences and knowledge about Balinese traditional games as well as the heads of governmental sectors especially in the field of tourism and culture. The results of the study provides an overview of the following: there are external and internal factors why Balinese traditional games need to be revitalized. The external factor is connected with globalisation which has been bringing modern digital games. The internal factor comes from socio-cultural change, especially in the advanced development of civilization. Because of those factors, revitalization of Balinese traditional games is needed through cultural attraction festival which can attract local community and tourists to participate.